Beep : a novel - Roorbach, Bill (Algonquin Books of Chapel Hill, 2024)
"An ebullient, funny novel about the friendship between a brilliant young girl and a perceptive squirrel monkey, the power of youth, and the way forward for a planet in crisis"--